2018
DOI: 10.14814/phy2.13821
|View full text |Cite
|
Sign up to set email alerts
|

ACE inhibition for severe bronchopulmonary dysplasia - an approach based on physiology

Abstract: Premature infants have a high incidence of bronchopulmonary dysplasia (BPD). Systemic hypertension, arterial thickness and stiffness, and increased systemic afterload may all contribute to BPD pathophysiology by altering left ventricular (LV) function and increasing pulmonary venous congestion by lowering end‐diastolic compliance. This case series studied the usefulness of angiotensin‐converting enzyme (ACE) inhibition by measuring clinical and echocardiographic improvements in six consecutive infants with “se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 62 publications
0
11
0
1
Order By: Relevance
“…39 In a case series of 6 infants (born at 23-29 weeks of gestation) with hypertension associated with severe chronic lung injury, captopril, an angiotensin-converting enzyme inhibitor, improved respiratory and cardiac indices 5 to 7 weeks after birth. 40 Ischemic heart disease. A populationbased cohort study found that adults ages 30 to 43 who were born preterm (gestational age < 37 weeks) have a 53% increased relative risk of ischemic heart disease compared with a fullterm birth cohort, and those born early term (37 to 38 weeks) have a 19% increased risk.…”
Section: Early Antenatal and Postnatal Exposures May Have Lifelong Health Implications Pravia And Bennymentioning
confidence: 99%
“…39 In a case series of 6 infants (born at 23-29 weeks of gestation) with hypertension associated with severe chronic lung injury, captopril, an angiotensin-converting enzyme inhibitor, improved respiratory and cardiac indices 5 to 7 weeks after birth. 40 Ischemic heart disease. A populationbased cohort study found that adults ages 30 to 43 who were born preterm (gestational age < 37 weeks) have a 53% increased relative risk of ischemic heart disease compared with a fullterm birth cohort, and those born early term (37 to 38 weeks) have a 19% increased risk.…”
Section: Early Antenatal and Postnatal Exposures May Have Lifelong Health Implications Pravia And Bennymentioning
confidence: 99%
“…Infants with severe BPD can experience both systemic and pulmonary hypertension which contributes to their respiratory and cardiovascular morbidity [38]. Infants with severe BPD and pulmonary hypertension are at greater risk of mortality [39].…”
Section: Pulmonary Vasodilatorsmentioning
confidence: 99%
“…The incidence of systemic hypertension has been variously reported to be between 7 and 43% [38]. Infants have increased aorta wall thickness and stiffness [50], hypertrophy of the heart and reduced cardiac function [51].…”
Section: Anti-hypertensivesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relationship between the impact on LV function, systemic hypertension, and respiratory morbidity is poorly understood. There is preliminary evidence that Angiotensin Converting Enzyme (ACE) inhibitors may have a positive modulator role on LV diastolic function in neonates [ 13 ]. Since July 2020, infants with systemic hypertension and concern for LV diastolic dysfunction at our institution have received treatment with a long-acting ACE inhibitor, enalapril, according to a standardized protocol and strict serial Targeted Neonatal Echocardiography (TnECHO) monitoring.…”
Section: Introductionmentioning
confidence: 99%